THE PROCESS OF RESILIENCE IN WOMEN WHO WERE VICTIMS OF SEXUAL VIOLENCE: A POSSIBILITY FOR CARE - Lucimara Fabiana Fornari; Liliana Maria Labronici (Universidade Federal do Paraná, 2018)
Objective: To investigate the process of resilience in women who were victims of sexual violence. Method: Exploratory, qualitative research, grounded in the concept of resilience, undertaken with 12 women who were victims of sexual violence, who were attended in the Specialized Care Service and in a Women's Police Office, in a municipality in the Brazilian state of Paraná, between September 2013 and February 2014. The content of the semistructured interviews was subjected to thematic content analysis. Results: The feeling of care and responsibility promoted internal mobilization - the beginning of the process of resilience. The presence of people inclined to listen without judging made it possible to represent the trauma experienced by the participants. Re-linking with God and reactivation of faith provided encouragement for believing that surviving was more relevant than being a victim. Final considerations: The study allowed the construction of knowledge related to the resilience of women who were victims of sexual violence, and showed the importance of incorporating this topic into nursing care.